Keabsahan Akad Jual Beli Online Muslim Kelas Menengah Kota Yogyakarta Pasca Pandemi Covid-19 - Muzalifah, Muzalifah (Sharia Faculty Islamic Economic Law Study Department, 2021)
This study aims to determine the validity of the online buying and selling contract after the Covid-19 pandemic. Online buying and selling transactions are increasingly prevalent and have become superior after the Covid-19 pandemic. One of the factors is the government ban on crowds and encouragement to always maintain a safe distance to avoid Covid-19. This study uses a quantitative approach. The data collection technique used a questionnaire distributed to 45 respondents who carried out buying and selling online after the Covid-19 pandemic. Meanwhile, the data analysis used percentages. The results of the study found that only 8.9% of 45 respondents stated that they were buying and selling online to avoid the spread of Covid-19, 22.2% of them stated that online buying and selling was profitable, and 26.7% for easier marketing. While the rest said that buying and selling online was done to save business capital and as a side job. According to Islamic law, there is no prohibition on buying and selling activities after the Covid-19 pandemic as long as it does not conflict with Islamic teachings. The contract in the sale and purchase is valid if it meets the requirements and is in harmony according to Islamic law. The application of khiyar rights in online buying and selling after the Covid-19 pandemic is important to implement. This is done to avoid a loss to one of the parties after the transaction process has taken place.